2012
DOI: 10.1002/elsc.201100076
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biogas yield from energy crops with rumen anaerobic fungi

Abstract: Anaerobic fungi (AF) are able to degrade crop substrates with higher efficiency than commonly used anaerobic bacteria. The aim of this study was to investigate ways of use of rumen AF to improve biogas production from energy crops under laboratory conditions. In this study, strains of AF isolated from feces or rumen fluid of cows and deer were tested for their ability to integrate into the anaerobic bacterial ecosystem used for biogas production, in order to improve degradation of substrate polysaccharides and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…In contrast, the direct incorporation of anaerobic fungi into these bioreactors would eliminate the requirement of an aerobic predigestion. Incorporation of anaerobic fungi in bioreactors improved biogas yield for up to 10 days postinoculation, enhancing yield by 4–22% depending on the substrate and fungal species used (Fliegerova et al ., ; Procházka et al ., ). Unfortunately, the inability of anaerobic fungi to survive long term in fermenters, however, makes the application of anaerobic fungi in commercial full‐scale biogas production systems unfeasible using current technologies (Procházka et al ., ).…”
Section: Biotechnological Applicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, the direct incorporation of anaerobic fungi into these bioreactors would eliminate the requirement of an aerobic predigestion. Incorporation of anaerobic fungi in bioreactors improved biogas yield for up to 10 days postinoculation, enhancing yield by 4–22% depending on the substrate and fungal species used (Fliegerova et al ., ; Procházka et al ., ). Unfortunately, the inability of anaerobic fungi to survive long term in fermenters, however, makes the application of anaerobic fungi in commercial full‐scale biogas production systems unfeasible using current technologies (Procházka et al ., ).…”
Section: Biotechnological Applicationsmentioning
confidence: 97%
“…A promising source of renewable, environmentally friendly energy is the production of biogas from the anaerobic digestion of organic waste. Currently used bioreactors display somewhat low degradation of organic material (40–60%) (Procházka et al ., ) thus, technologies that can improve this efficiency are needed. The biological pretreatment of crop residues with white and brown rot fungi has been shown to be effective at improving biogas production (Ghosh & Bhattacharyya, ).…”
Section: Biotechnological Applicationsmentioning
confidence: 99%
“…In contrast, Procházka et al. observed that rumen cultivable fungi do not exhibit long‐term survival in biogas fermenters.…”
Section: Discussionmentioning
confidence: 93%
“…The current results are consistent with the view of McGranaghan et al [43] that many fungi remain viable in the anaerobic environment of cattle feces, slurries, and manures for long periods. In contrast, Procházka et al [22] observed that rumen cultivable fungi do not exhibit long-term survival in biogas fermenters.…”
Section: Ergosterol and Amino Sugar Concentrations In Slurriesmentioning
confidence: 92%
“…These natural polymers interact closely together and create a complex matrix that is rather resistant to biotic and abiotic degradation, especially under anaerobic conditions (Adney et al 1991;Prochazka et al 2012). Cellulose constitutes a major component of plant biomass, consisting of β(1→4) glycosidic bonds connected D-glucose units.…”
Section: Introductionmentioning
confidence: 99%